Takaki Noriko's Social Conflict in the Novel Zettai Seigi by Akiyoshi Rikako - Tia Ristiawati; Viana Meilani Prasetio; Nadia Ilma Dewi (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2022)
This research uses the novel titled Zettai Seigi by Akiyoshi Rikako as the object of research. The purpose of this research is to analyze the social conflict and characterization of Noriko. The author uses the simak-catat method to collect the data and content analysis method to analyze the data, afterwards the data were analyzed using Soekanto's theory of social conflict and Jauhari's theory of characterization. Based on the results of the analysis, Noriko has 14 forms of characterization. Then, the form of social conflict is personal conflict, and the cause of social conflict is due to differences in ways of thinking between individuals, application of truth by Noriko, Noriko's character who always demands perfection, and in ethics and moral terms. In this novel, the author of the novel wants to show the reader that when in society, don't be a person who demands perfection, always meddling in other people's business, and don't build a character like the one that Noriko has because it will interfere with the social life of others. Furthermore, the law was created as a means to educate the public, not to drag everything into the realm of law.